Cost Control Recommendation Based on Activity-Based Management: A Case Study from Decreasing Opportunity Cost of National Health Insurance - Lutfiana Rakhmawati; Sony Wijaya; Nyoman Anita Damayanti; Thinni Nurul Rochmah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background:  Opportunity cost is a loss caused by either income or other activities that are not carried out and can potentially be lost due to waiting for prescription services.  In the hospitals in Surabaya, it is known that, the waiting time for patient prescription services that utilize national health insurance in outpatient pharmacies exceeds the minimum service standards. Aims:  to analyse the opportunity loss and cost of patients utilizing the National Health Insurance from prescription service activities in which the recommendation cost control can be designed. Methods: A case study using an observational approach has been applied concerning activity-based management theory for defining non-value-added activities. Opportunity cost is converting the waiting time for prescription services to the income lost while waiting for the prescription. 120 patients who use national health insurance for obtaining prescriptions were recruited. Data were analysed using an observational table and calculated the service process and activity process. Results: Patient's opportunity loss for concoction drugs is 75.01 minutes, chronic non-concoction drugs are 71.14 minutes and non-chronic finished drugs are 46.3 minutes. The patient average opportunity cost based on the type of work and clustered by diseases, namely civil servants (IDR. 125,088 for Concoction Medicine), Pensioners (IDR. 87,800 for all typical medicine), housewives (IDR. 146,500 for all typical medicine), private employees (IDR. 136,878.20 for Concoction Medicine), and self-employed (IDR. 172,624.45 for Concoction Medicine). Conclusions:  The findings suggest the recommendation for cost control through optimizing cost management and procurement of incentive programs if opportunity costs fall.Abstrak: Latar Belakang: Opportunity cost adalah kerugian yang disebabkan oleh pendapatan atau kegiatan lain yang tidak dilakukan dan berpotensi hilang karena menunggu jasa resep.  Di rumah sakit di Surabaya, diketahui bahwa, waktu tunggu layanan resep pasien yang memanfaatkan jaminan kesehatan nasional di apotek rawat jalan melebihi standar pelayanan minimal. Tujuan: untuk menganalisis kehilangan peluang dan biaya pasien yang menggunakan Jaminan Kesehatan Nasional dari kegiatan layanan resep di mana kontrol biaya rekomendasi dapat dirancang.  Metode: Studi kasus menggunakan pendekatan observasional telah diterapkan mengenai teori manajemen berbasis aktivitas untuk mendefinisikan kegiatan non-nilai tambah. Biaya peluang didefinisikan sebagai mengubah waktu tunggu untuk layanan resep menjadi pendapatan yang hilang saat menunggu resep. 120 pasien yang menggunakan asuransi kesehatan nasional untuk mendapatkan resep direkrut. Data dianalisis menggunakan tabel observasional dan dihitung proses pelayanan dan proses kegiatan.  Hasil: Peluang kerugian P atient untuk obat racikan adalah 75,01 menit, obat non-racikan kronis adalah 71,14 menit dan obat jadi non-kronis adalah 46,3 menit. Rata-rata biaya kesempatan pasien based pada jenis pekerjaan dan dikelompokkan oleh penyakit, yaitu pegawai negeri sipil (IDR.  125.088 untuk Obat Ramuan), Pensiunan (IDR.  87.800 untuk semua obat khas), ibu rumah tangga (IDR. 146.500 untuk semua obat khas), karyawan swasta (IDR.  136.878. 20 untuk Obat Ramuan), dan wiraswasta (IDR. 172.624. 45 untuk Obat Ramuan). Kesimpulan: Temuan menunjukkan rekomendasi untuk pengendalian biaya melalui optimalisasi manajemen biaya dan pengadaan program insentif jika biaya peluang turun.